The Effect of Information Technology Utilization and Employee Competence on Employee Performance with Job Satisfaction as the Intervening Variable in the Aceh Irrigation Service - Yanita; Yusniar; Iis, Em Yusuf; Abubakar, Rusydi; Maimunah, Siti (International Journal of Professional Business Review, 2023)
Purpose:  This research examines the influence of the use of information technology and employee competence on employee performance, with job satisfaction as an principal adaptable at the Aceh Irrigation Service located in Jl. Ir. H. Mohd Thaher No. 18 Lueng Bata, Banda Aceh.